Hydrological Criterion of Sedimentation Processes in the Iraqi Dams - الطائي, ثائر محمود (Latakia University Journal -Engineering Sciences Series, 2019)
Six dam sites on Tigris river and its tributaries (the Greater and the Lesser zab rivers) were chosen as a case study to predict the hydrological criterion of sedimentation processes in their reservoirs such as trap efficiency, sedimentation index and their impact on the annual storage loss according the predicted sediment yield. The studied reservoirs were classified hydrologically and topographically according to the classification of reservoirs predicted by many scientists interested in dams engineering. Hydrologically, the studied reservoirs were classified either seasonal or hold over storage reservoirs in which almost all the studied reservoirs were classified as seasonal storage reservoirs. Topographically they were classified either gorge or hill or flood plain foothill types. The research work concluded that the trap efficiency values of the studied Iraqi dams ranged between 0.6 to 0.84. It increased in accordance with the increase of sedimentation index, the capacity inflow ratio and the retention period. Moreover, there is a strong relation between the trap efficiency values and the narrowness and depths of the reservoirs. Finally the annual storage loss due to the sedimentation in the studied dams was predicted to be in a range of ( 0.1 to 0.84) percentages. اختيرت ستة خزانات للسدود المنشاة على نهر دجلة وروافده كحالة دراسية لتعيين المعايير الهيدرولوجية لعمليات الترسيب مثل كفاءة الترسيب، دليل الترسيب وتأثيرها في فقدان السعة الخزنية السنوية استنادا إلى الإنتاج الرسوبي المخمن. صنفت الخزانات قيد الدراسة هيدرولوجيا وطوبوغرافيا حيث تم تصنيفها هيدرولوجبا إلى خزانات موسمية وخزانات ذات خزن طويل الأمد، كما صنفت طوبوغرافيا إلى ثلاثة أنواع وهي الوادي الضيق والهضاب وأقدام السهول الفيضية. خلص البحث إلى أن قيمة كفاءة الترسيب في السدود العراقية قيد الدراسة تراوحت بين (0.6 إلى0.98 ) وتزداد هذه القيمة مع زيادة دليل الترسيب وبزيادة النسبة بين السعة الخزنية ومعدل الجريان الداخل السنوي وكذلك مع زيادة زمن الاحتجاز وإن هنالك علاقة كبيرة بين كفاءة الترسيب مع تضيق شكل الخزان وعمقه. كما تراوحت قيمة المتنبأ بها للفقدان السنوي لحجم الخزان بسبب الترسيب في هذه الخزانات مابين (0.1 إلى 0.84) %. كما تراوحت النسبة بين زمن الاحتجاز ومعدل سرعة الجريان في الخزان ما بين( 8 1.6*10 إلى 8 ( 8*10متر-1.